A 12-month longitudinal study of Listeria monocytogenes contamination and persistence in pork retail markets in China. (June 2017) - Luo, Lijuan; Zhang, Zhengdong; Wang, Hong; Wang, Pengfei; Lan, Ruiting; Deng, Jianping; Miao, Yimao; Wang, Yan; Wang, Yi; Xu, Jianguo; Zhang, Ling; Sun, Songsong; et al.
Abstract: Listeria monocytogenes is a foodborne pathogen frequently isolated from raw pork meat. This study was designed to investigate the prevalence and molecular characteristics of L. monocytogenes in raw pork from open markets in China. The survey was conducted monthly over a 12-month period in Zigong, China. L. monocytogenes was isolated from 262 of 1641 samples collected (16.0%) including minced meat samples (131/608, 21.5%), pork pieces samples (111/857, 13.0%) and environmental swabs (20/176, 11.4%). The isolation rates in spring and winter were significantly higher than those in summer and autumn ( X 2  = 68.85, P < 0.05). All isolates were subjected to serotyping, multi-locus sequence typing (MLST) and AscI pulsed-field gel electrophoresis (PFGE). The 262 isolates were subtyped into five serotypes: 1/2b (43.1%), 1/2c (35.5%), 1/2a (19.1%), 4b (1.1%), 3a (1.1%); 20 sequence types (STs) with four most frequent STs, being ST9 (35.9%), ST87 (19.8%), ST3 (16.0%) and ST8 (14.1%); and 39 pulsotypes (PTs) with PT4 (26.3%), PT30 (14.5%) and PT11 (12.6%) being most frequent. Two primary pulsotypes from pork pieces were previously isolated from clinical listeriosis cases in the local hospitals. The six markets from different districts differed in the level of contamination and strain types. Persistent contamination of L. monocytogenes was found in the markets especially in meat mincers, which were found to be one likely source of continuous cross contamination. These findings will help develop strategies to reduce L. monocytogenes contamination in open markets for better public health control and prevention of foodborne L. monocytogenes infections. Highlights: Seasonal variation of L. monocytogenes prevalence was observed. Prevalence and genotype were different in the markets from different districts. Persistent contamination was found especially in meat mincers. Meat mincers can be a potential source of cross-contamination in retail markets.